2015
DOI: 10.3892/ol.2015.3800
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of frequency and severity of hypomagnesemia in patients with metastatic colorectal cancer treated with cetuximab, with a review of the literature

Abstract: Abstract. Currently, there are a few systemic treatment options for patients with metastatic colorectal cancer (mCRC). Targeted therapy used in this setting includes the use of monoclonal antibodies, such as cetuximab or panitumumab, directed against epidermal growth factor receptor. The aim of the present study was to estimate the frequency and severity of hypomagnesemia among patients with mCRC treated with cetuximab. The data from the Department of Clinical Oncology, University Hospital of Krakow (Krakow, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Of the cases, 22% were grade 1 (i.e., below the lower limit of normal to 1.2 mg/dl). 57 There was no statistically significant correlation between Mg level and patient age, duration of treatment, localization of primary tumor or metastases, and number of metastases. However, there was an upward trend in a logistic regression model showing that the risk of developing hypomagnesemia increases with age.…”
Section: Epidermal Growth Factor Receptor−1 Target Inhibitorsmentioning
confidence: 78%
See 1 more Smart Citation
“…Of the cases, 22% were grade 1 (i.e., below the lower limit of normal to 1.2 mg/dl). 57 There was no statistically significant correlation between Mg level and patient age, duration of treatment, localization of primary tumor or metastases, and number of metastases. However, there was an upward trend in a logistic regression model showing that the risk of developing hypomagnesemia increases with age.…”
Section: Epidermal Growth Factor Receptor−1 Target Inhibitorsmentioning
confidence: 78%
“…However, there was an upward trend in a logistic regression model showing that the risk of developing hypomagnesemia increases with age. 57 Management of EGFR inhibitor−induced hypomagnesemia is summarized by Fakih in a review. 58 One has to ensure that the patient is not on any other offending medication, such as thiazide diuretics or proton pump inhibitors.…”
Section: Epidermal Growth Factor Receptor−1 Target Inhibitorsmentioning
confidence: 99%
“…Hypomagnesemia is negatively associated with age, potentially due to the easier loss of Mg 2+ ( 61 , 62 ). Furthermore, severe hypomagnesemia may lead to changes in muscle strength (including cramps, muscle weakness and ataxia), heart lesions (including coronary spasms, arrhythmia and long Q-T syndrome) and psychotic symptoms (including epilepsy, insanity, depression and anxiety) ( 63 ).…”
Section: Egfr Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Univariate logistic regression analyses were conducted to assess odds ratios (ORs) and 95% confidence intervals (CIs). Previously reported potential risk factors for hypomagnesemia, including PPI use, 6) age, 7) renal impairment, 8) and diuretics, 9) were examined. In before the propensity score-matched cohort, factors of p < 0.25 in univariate analyses were evaluated as potential covariates in a stepwise multivariate logistic regression with backward selection.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified other risk factors for hypomagnesemia, including the use of proton pump inhibitors (PPIs), 6) age, 7) renal impairment, 8) and diuretics. 9) Several reports have highlighted that concomitant use of PPIs can elevate the risk of hypomagnesemia in cancer patients receiving panitumumab and cetuximab.…”
Section: Introductionmentioning
confidence: 99%